Asset Seizure Regulations Against Public Officials with Unexplained Wealth (A Comparative Study of the Philippines and Australia) - Dewa Ayu Susanti Dewi; Ni Gusti Agung Ayu Mas Tri Wulandari; Luh Putu Yeyen Karista Putri (Jurnal Pembangunan Hukum Indonesia, 2025)
The Draft Law on Asset Seizure, which includes the concepts of unexplained wealth and non-conviction based (NCB), is a regulation that urgently needs to be passed in Indonesia. This is due to the increasing losses suffered by the state as a result of corruption involving public officials. This legal instrument will strengthen the state's efforts to execute assets derived from corruption without having to wait for a final and binding court decision. Several countries have successfully implemented this concept, including Singapore and the Philippines, in order to accelerate the process of confiscating the assets of corruptors. This study aims to examine the regulations on asset reporting by public officials in uncovering unexplained wealth and to review the regulations on asset confiscation from officials based on unexplained wealth in Indonesia, Australia, and the Philippines. The method used is a normative approach with comparative legal analysis. The results of the study show that Australia, through the Unexplained Wealth Order (UWO), and the Philippines, through Republic Act No. 1379, have regulated the mechanism for seizing assets without waiting for the completion of criminal proceedings. This proves that the NCB approach is effective in combating illegal wealth. The conclusion of this study is that Indonesia needs to immediately pass the Asset Seizure Bill by applying the concepts of unexplained wealth and NCB as in Singapore and the Philippines so that corruption enforcement is more optimal and in line with international practices.